2013
DOI: 10.1371/journal.pone.0057176
|View full text |Cite
|
Sign up to set email alerts
|

Sino-Canadian Collaborations in Stem Cell Research: A Scientometric Analysis

Abstract: BackgroundInternational collaboration (IC) is essential for the advance of stem cell research, a field characterized by marked asymmetries in knowledge and capacity between nations. China is emerging as a global leader in the stem cell field. However, knowledge on the extent and characteristics of IC in stem cell science, particularly China’s collaboration with developed economies, is lacking.Methods and FindingsWe provide a scientometric analysis of the China–Canada collaboration in stem cell research, placin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…The following indicators were used to measure the possible relationships. Salton’s measure of research collaboration strength between two countries (Ali-Khan, Ray, McMahon, & Thorsteinsdóttir, 2013; Glänzel, Janssens, & Thisjs, 2009): where N i is the total number of contributions of country i, N j is the total number of contributions of country j, and N ij is the total number of joint contributions by country i and country j. N i + N j : sum of total contributions by country i and total contributions by country j. 2012 Import and export volume of all commodities between country i and country j (Im/Export): We based our computation on the data from United Nations Commodity Trade Statistics Database (2013). Distance: theoretical great-circle distance between two capitals of country i and country j. NetUser: mean of the Internet users per 100 people in country i and country j in 2011 (The World Bank, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…The following indicators were used to measure the possible relationships. Salton’s measure of research collaboration strength between two countries (Ali-Khan, Ray, McMahon, & Thorsteinsdóttir, 2013; Glänzel, Janssens, & Thisjs, 2009): where N i is the total number of contributions of country i, N j is the total number of contributions of country j, and N ij is the total number of joint contributions by country i and country j. N i + N j : sum of total contributions by country i and total contributions by country j. 2012 Import and export volume of all commodities between country i and country j (Im/Export): We based our computation on the data from United Nations Commodity Trade Statistics Database (2013). Distance: theoretical great-circle distance between two capitals of country i and country j. NetUser: mean of the Internet users per 100 people in country i and country j in 2011 (The World Bank, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, in order to have an intuitively clearer representation with a mathematical meaning (see, Eqs. [1][2][3][4][5][6][7][8]), the authors proposed to use the graphical metric based on the 'square surface areas' which represents subsurface structural boundary for the documents published by 'A' or 'B' systems, and the co-publication produced together.…”
Section: A-bmentioning
confidence: 99%
“…In particular, it is well known that the number of co-publications is typically employed as an indicator of collaboration in a wide range of subjects at every level. It is quite clear that many studies have appeared in the academic literature with their attention focused on the national trend of co-publication productivity on the most varied subjects [8][9][10][11][12][13][14] . Ali-Khan et al [8] provided a scientometric analysis of the China-Canada collaboration in stem cell research publications indexed in Scopus database and examined collaboration levels, collaboration preferences, scientific impact, the collaborating institutions in China and Canada, areas of mutual interest, and funding sources and found that China-Canada collaboration is rising steadily; enhanced the impact of collaborated publications as compared to papers authored solely.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[17] This field is characterized by its highly collaborative nature and number of scientific disciplines interrelated by stem cell research lends it an exciting yet complicated character. [9,18,13] There are few studies on the intellectual structure of stem cell research in developing countries. [19] and the only scientometric analysis of stem cell research in India has been conducted by Karpagam et al [20] This study explores the trends in Stem Cell research in India during 1990-2014 using Scopus database.…”
Section: Previous Studiesmentioning
confidence: 99%